2019
DOI: 10.1098/rsos.190869
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and thermal degradation properties of hyperbranched polyisoprene prepared by anionic polymerization

Abstract: Hyperbranched polyisoprene was prepared by anionic copolymerization under high vacuum condition. Size exclusion chromatography was used to characterize the molecular weight and branching nature of these polymers. The characterization by differential scanning calorimetry and melt rheology indicated lower Tg and complex viscosity in the branched polymers as compared with the linear polymer. Degradation kinetics of these polymers was explored using thermogravimetric analysis via non-isothermal techniques. The pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 73 publications
2
9
0
Order By: Relevance
“…47,48 Note that we relate our values of E a to the viscous dissipation of the PF-GO composite and not the thermooxidative processes and hemolytic dissociation of crosslinked bridges between PF and GO as reported otherwise. 49 Comparing the rheological response of our PF/m-GO samples to petroleumbased elastomers, such as styrene-butadiene rubbers and hyperbranched polyisoprene, our values of G 0 over the corresponding unshied frequency range and h are found in a good agreement to the studies, 47,50,51 reporting shear thinning behavior and strong elastic response as shown in Fig. 6.…”
Section: Runsupporting
confidence: 84%
“…47,48 Note that we relate our values of E a to the viscous dissipation of the PF-GO composite and not the thermooxidative processes and hemolytic dissociation of crosslinked bridges between PF and GO as reported otherwise. 49 Comparing the rheological response of our PF/m-GO samples to petroleumbased elastomers, such as styrene-butadiene rubbers and hyperbranched polyisoprene, our values of G 0 over the corresponding unshied frequency range and h are found in a good agreement to the studies, 47,50,51 reporting shear thinning behavior and strong elastic response as shown in Fig. 6.…”
Section: Runsupporting
confidence: 84%
“…Both P1 and P2 showed a greater dependency on angular frequency because of less branching and more chain entanglements. On the other hand, with short molecular chains and more branching in P3, it was difficult for the molecules to entangle; thus, they were less sterically hindered during flow and hence exhibited the lowest or no dependence on the angular frequency . It appeared to be more Newtonian than both P1 and P2.…”
Section: Resultssupporting
confidence: 66%
“…[64,65] Moukinha [64] suggests using model-free analyses to obtain a satisfactory decomposition model for either separated-step or single-step processes. The widely accepted Friedman method [66,67] investigates degradation kinetics at heating rates not achievable in TGA measurements, as presented in additive manufacturing. It is based on a set of multiple linear heating rates and derives a semi-empirical rate law to predict degradation behavior.…”
Section: Polymer Degradationmentioning
confidence: 99%